Prioritizing districts in India for buffalo development - KUMAR, ANIL; KUSHWAHA, B P (The Indian Journal of Animal Sciences, 2015)
Prioritization of districts for buffalo development in India was done taking into account the buffalo growth rate (r), density (d) and number per 1,000 human beings (PTH). Priority Index for buffalo (PI-B) was worked out by giving equal weight to the 3 variables. Analysis was done for 19 states with 311 districts for the period 1966 to 2007, taking 1966 as the base year and apportioning the subsequent data to the base year. The 19 states covered 90.53% of the geographical area having 98.7% of the total buffalo population. Zones I to IV were demarcated each having 25% of the total buffalo population based on decreasing order growth rate, density, PTH and PI-B. Based on the Priority Index, 25% of the buffaloes with highest index (Z- I) were reared in 31 districts in 6.74% of the geographical area of the country by 9.37% of human beings. This zone had an overall growth rate of 2.70% p.a., buffalo density 124 and 245 buffalo PTH. Zone II with next 25% of buffaloes were located in 51 districts in 14.6% area of the country where 14.8% of human beings reside. This zone had an overall growth rate of 2.15% p.a., buffalo density 57 and 154 buffalo PTH. Zone III with next 25% of buffaloes were located in 67 districts in 19.7% area of the country where 22.4% of human beings reside. This zone had an overall growth rate of 1.86% p.a., buffalo density 42 and 102 buffalo PTH. Zone IV with next 23.7% of buffaloes were located in 162 districts in 49.5% area of the country where 49.4% of human beings reside. This zone had an overall growth rate of 0.54% p.a., buffalo density 16 and 44 buffalo PTH. GIS maps were also prepared for visualization of the location of different zones based on growth rate, density, PTH and Priority Index for buffalo.